Comparison of Fatness and Meat Quality of Kampung Chickens, Arabic Chickens and Laying Type Cockerels at Different Slaughtering Ages - Tamzil , M.H. (International Journal of Poultry Science, 2017)
Background and Objective: Fat levels affect meat quality. This study aimed to determine the level of abdominal fat deposits, fat carcass and meat quality of Kampong, Arabic and laying type cockerels. Methodology: The study used a completely randomized design with a 3×7 factorial arrangement. The first factor was the type of chicken and consisted of 3 levels (laying type cockerels, Kampong chickens and Arabic chickens). The second factor was slaughter ages and consisted of 7 levels (chickens 4, 5, 6, 7, 8, 9 and 10 weeks old). A total of 63 day-old chicks (DOCs) of laying type cockerels, 63 DOCs of unsexed Arabic chickens and 63 DOCs of unsexed Kampong chickens were divided into 9 groups, each group consisted of 7 DOCs. Parameters included the weight of abdominal fat, the fat of the meat, water holding capacity, pH, cooking loss and meat tenderness. Data obtained were analyzed using analysis of variance and LS-MEAN advance tests. Results: Results of the study showed that the type of chicken affected levels of abdominal fat (p<0.01), the fat level of meat (p<0.05), water holding capacity and cooking loss (p<0.05), but did not affect the pH value and the meat tenderness (p>0.05). Slaughter age increased the level of abdominal fat (p<0.01), the fat level of meat (p<0.05), water holding capacity, cooking loss (p<0.01) and meat tenderness (p<0.05). However, there was no interaction between types of chicken and slaughter age across all observed variables (p>0.05). Conclusion: Meat quality of Kampong and Arabic chickens were lower than that of laying type cockerels. Meat quality decreased with slaughtering age.